Abstract Society in the Time of Plague. Issue 4 (July 2020) - Chmielewski, Adam
The global lockdown following the outbreak of the COVID-19 pandemic is likely to generate all sorts of consequences: psychological, social, economic, and political. To hypothesize about what will emerge from the present situation is at this point both premature and impossible. The impossibility comes primarily from the gravity and vastness of this emergency and from the lack of intellectual resources to deal with the challenge. At the same time, however, the need to get a grasp of the condition in which we have found ourselves is both understandable and irresistible. One way of responding, at least partially, to the demand and its possible consequences may be to refer to the concept of abstract society, an idea formulated 75 years ago by the Austrian-British philosopher Karl Popper.